2015
DOI: 10.4236/ojf.2015.54028
|View full text |Cite
|
Sign up to set email alerts
|

Forestry under Climate Change. Is Time a Tool for Sustainable Forest Management?

Abstract: Changing climate conditions are known to influence forest tree growth response and the CO2 cycle. Dendroclimatological research has shown that the climate signal, species composition, and growth trends have changed in different types of forest ecosystems during the last century. Under current and demonstrated changes in climate variability at the geographic, regional, and local levels tree growth shows also variability and trends that can be non-stationary during time even at relatively short distance between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…In particular, we studied habitat “9210(*) Apennine beech forests with Taxus and Ilex ”, listed as of priority interest for conservation in the Annex I of the EU Habitats Directive. Anthropic pressures such as the intensification of sylvicultural management and climate change with increasing temperatures and drought are threatening the maintenance of such forests in a good conservation status in central Apennines 7 10 , as required by the Directive 92/43/EEC. For such reasons, there is the need to develop new and repeatable monitoring strategies that take account of the many indicators of the conservation status and naturalness of beech forests, such as their floristic composition, structural features like the dimensions of trees and the amount of dead wood, and the amount of litter, mosses, and lichens 5 .…”
Section: Background and Summarymentioning
confidence: 99%
“…In particular, we studied habitat “9210(*) Apennine beech forests with Taxus and Ilex ”, listed as of priority interest for conservation in the Annex I of the EU Habitats Directive. Anthropic pressures such as the intensification of sylvicultural management and climate change with increasing temperatures and drought are threatening the maintenance of such forests in a good conservation status in central Apennines 7 10 , as required by the Directive 92/43/EEC. For such reasons, there is the need to develop new and repeatable monitoring strategies that take account of the many indicators of the conservation status and naturalness of beech forests, such as their floristic composition, structural features like the dimensions of trees and the amount of dead wood, and the amount of litter, mosses, and lichens 5 .…”
Section: Background and Summarymentioning
confidence: 99%
“…Forest research has shown that climate variability plays a relevant role in forest planning and management under climate change [4,18,69] as it influences the response(s) of forest and tree growth and the CO2 cycle. Changing climate conditions can alter the temperature and/or precipitation thresholds critical to forest tree growth.…”
Section: Time As a Key Factor In Climate Change And Tree Growthmentioning
confidence: 99%
“…Periods of increase and decrease of stand growth crossed with a suitable range of temperature and/or rainfall thresholds for tree growth can identify time and period suitable for silvicultural interventions in forest planning and management. Source: [4].…”
Section: Tree Ring Growth and Periodicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature and precipitation are the most informative climatic factors that determine not only the radial annual growth of tree stems, but also the biological productivity of forest stands (DeLucia et al, 2000;Ni et al, 2001;Stegen et al, 2011;D' Aprile et al, 2015;Fang et al, 2016). Analysis of the results of such studies revealed significant contradictions and uncertainties about the assessment of these indices' dependence on temperature and precipitation using both empirical and functional models (Eggers et al, 2008;Shuman, Shugart, 2009;Poudel et al, 2011;Han et al, 2018).…”
Section: Introductionmentioning
confidence: 99%